What have we learnt from 'good language learners'?. (6th August 2015) - Griffiths, Carol
Abstract: This year marks the fortieth anniversary of the publication of two landmark articles concerning the 'good language learner'. In the years since, vigorous debate has revolved around both theoretical issues (including definition, classification, theoretical foundation, and the relationship of strategies to successful learning) and practical issues (including teachability and the relationship to learner, and contextual and target variables). This article reviews these areas and concludes that strategies are teachable, especially if teachers include both explicit and implicit instructional techniques in their programmes to raise awareness, provide practice, and encourage evaluation so that learners can reflect on their strategy use and adjust their strategy repertoires accordingly. A number of areas still requiring further investigation are suggested, especially further exploration of how strategies might be taught more effectively and seeking evidence that this makes a difference in terms of 'good language learning'.